Disease Activity and Conversion into Multiple Sclerosis after Optic Neuritis Is Treated with Erythropoietin - Sühs, Kurt-Wolfram (Int J Mol Sci, 2016)
Changes in cerebral lesion load by magnetic resonance imaging (MRI) in patients from a double-blind, placebo-controlled, phase II study on erythropoietin in clinically isolated optic neuritis (ClinicalTrials.gov, NCT00355095) were analyzed. Therefore, patients with acute optic neuritis were assigned to receive either 33,000 IU of recombinant human erythropoietin (IV) daily for three days, or a placebo, as an add-on to methylprednisolone. Of 35 patients, we investigated changes in cerebral lesion load in MRIs obtained at baseline and at weeks 4, 8, and 16. In 5 of the 35 patients, we found conversion into multiple sclerosis (MS) based on MRI progression only. These five patients had received the placebo. Another five patients showed MRI progression together with relapses. Three of these patients had received erythropoietin, and two the placebo. Yet, analyzing the change in absolute numbers of periventricular, juxtacortical, and infratentorial lesions including gadolinium-enhancing lesions, there were no significant differences between the groups. Although effective in terms of retinal nerve fiber layer protection, erythropoietin treatment of acute isolated optic neuritis did not influence further evolution of MRI lesions in the brain when comparing absolute numbers. However, early conversion from clinically isolated syndrome to MS assessed by MRI activity seemed to occur more frequently in the placebo-treated group.